1989
DOI: 10.1097/00000658-198902000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Alimentary Tract Duplications

Abstract: Alimentary tract duplications are unusual anomalies that may require surgical intervention in the neonate, infant, and occasionally in the older child. The clinical presentation of patients with alimentary tract duplications includes bleeding, abdominal pain, intussusception, and respiratory distress, or it may be an incidental finding on either abdominal examination or chest x-ray. A review of 96 patients with 101 duplications seen over the last 37 years is reported herein. Twenty-one duplications were confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
220
1
20

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(248 citation statements)
references
References 12 publications
4
220
1
20
Order By: Relevance
“…Duplications at the IC junction are a particular entity, not clearly identified in all the reported series [5][6][7][8] and generally included into the ileal duplications [9]. Only few Authors described the IC type, for which the operative approach consisted of segmental resection with primary reanastomosis [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Duplications at the IC junction are a particular entity, not clearly identified in all the reported series [5][6][7][8] and generally included into the ileal duplications [9]. Only few Authors described the IC type, for which the operative approach consisted of segmental resection with primary reanastomosis [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal resection and anastomosis is required in all cases and include adjacent normal intestine because of common sharing of bowel wall and of blood supply [13,14]. Postoperative outcomes are often favorable.…”
Section: Discussionmentioning
confidence: 99%
“…If gastric ectopic mucosa is present, then acid secretion from this mucosa can result in peptic ulcer, perforation or bleeding. In one study [4], ectopic gastric mucosa was found in 21 duplications and pancreatic tissue was found in fi ve (out of 101). True duplication has all the layers of the parent gut.…”
Section: Structurementioning
confidence: 98%
“…Some of them may be confi ned to the thorax (21/ 101) [4]. Rarely, they can also present retroperitoneally.…”
Section: Sitementioning
confidence: 99%
See 1 more Smart Citation